Optimization of 4th generation distributed district heating system: Design and planning of combined heat and power. (January 2019) - Sameti, Mohammad; Haghighat, Fariborz
Abstract: This study applies a mathematical programming procedure to model the optimal design and planning of a new district which satisfies two features of the 4th generation district heating systems: energy reciprocity and on-site generation. The aim of the computational model is to investigate the effect of energy reciprocity (energy exchange among the buildings) as well as to find the best way to select the equipment among various candidates (capacities), the pipeline network among the buildings, and their electrical connections. The objective function includes the annualized overall capital and operation costs for the district along with the benefits of selling electricity to the grid. The distributed energy supply consists of heating, cooling, and power networks, several CHP technologies, solar array, chillers, and auxiliary boilers. The performance of the model for poly-generation was evaluated for designing the new part of Suurstoffi district situated in Risch Rotkreuz, Switzerland with seven residential and office complexes under four different scenarios. Allowing heat exchange among the buildings leads to 25% reduction in total annualized cost and 5% reduction in emission compared to the conventional districts. Removing the network and installation of PV and CHPs results in 9% reduction in emission and 11% reduction in cost. Simultaneous heat and electricity exchange results in a higher reduction in total annualized cost equal to 40% of the base scenario. Highlights: Optimal design of a new 4th generation district heating focusing on energy reciprocity. Selection, placement, operation of plants, and power and heating networks. Effects of heat and electricity exchange on total annualized cost and emission. Analysis of a real case study for 7 buildings in new part of Suurstoffi district. 40% reduction in cost and 11% reduction in CO2 emission in optimal design.